Systemization of knowledge inquiry in Islamic thought: the case of Al-Raghib Al-Asfahani - Shogar, Ibrahim Adam Ahmed (2014)
Creativity, innovation and problem solving are results of systematic inquiry. Inventions of nature are always superior to human inventions; therefore, human intellect observes the systems of the natural and human phenomena, based on two major modes of thinking styles: (1) the analytic mode that focuses on individual facts, and (2) synthetic mode which finds the reality at the collective level of the events. The first approach aims at finding the role of the individual parts in creating certain fact; while the second approach aims at identifying the interrelationship between the individual parts to find their major theme. Although both approaches are important in the process of scientific discovery; but the complicated problems of our time cannot be solved in one discipline but interdisciplinary approach. In other words, the systematic mind is essentially inclined to the second approach. The General Systems Theory (GST) and systemization of knowledge are some major approaches to create such a unified method of investigation. This paper aims to highlight the systemic mind in Islamic thought, with especial reference to al-Asfahani’s approach. Systematization of knowledge is a methodological process which aims at achieving one or more of the following goals: generating new knowledge, adding value to existing information, or inspiring new approach to understand the phenomenon from its various dimensions. The modern information science classifies the entire body of knowledge into four basic phases: data, information, knowledge, and wisdom. This mode of systemizing knowledge can be used for better understanding of the world. Abstraction and generalization are the major characteristics of the systematic mind. Many systematic thinkers were excelled throughout the history of Islamic thought; but this paper aims to study the case of al-Raghib al-Asfahani, who exhibited his systemic mind through many of his outstanding works, such as “al-Dhariyy`ah Ila Makarim al-Shari`ah” and “al-Mufradat Fi Gharib al-Qur`an”. The paper also highlights the crucial role of systemization of inquiry on creativity and innovation.